PENGARUH TEKNIK AUDIT BERBANTUAN KOMPUTER (TABK), INTEGRITAS, DAN KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT BPK RI PERWAKILAN ACEH - Islahil Akmalia; Nita Erika Ariani (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study aims to determine the effect TABK, integrity, and competency of auditor on audit quality of auditors at The Audit Board of The Republic of Indonesia (BPK RI-Aceh). This is a quantitative study with questionnaire used as the primary data elicitation and Likert scale as the measure. The populations in this study are all the auditors at the BPK RI-Aceh amount to 70 auditors. The sampling method using saturation sampling. Data analysis  method  use  is  multiple  linear  regression  analysis.  Results  of  the  study  show  TABK,  integrity,  and competency of auditor simultaneously has a significant effect on audit quality of auditors at the BPK RI-Aceh . The results also show that competency of auditor partially have a significant effect on audit quality of auditors at the BPK RI-Aceh, whereas TABK and Integrity have no significant effect on audit quality of auditors at the BPK RI- Aceh.